TINJAUAN HUKUM TERHADAP KEBIJAKAN DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK DI INDONESIA - Musa Darwin Pane; Rahim, Alvina (LPPM STAI Muhammadiyah Probolinggo, 2025)
The policy of diversion in the juvenile criminal justice system is a step forward in criminal law that aims to shift the resolution of children's cases from the formal judicial path to a restorative approach. This policy is based on the principle of the best protection for children and children's rights as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA). This study aims to analyse the legal basis, implementation, and challenges faced in the application of diversion in Indonesia. The research method used is a normative approach with a study of legislation and legal concepts. The results show that diversion is an effective mechanism for reducing the adverse effects of the judicial system on children and supports the achievement of restorative justice. However, in practice, obstacles are still found, such as a lack of understanding on the part of law enforcement officials, differences in the interpretation of legal provisions, and limitations in supporting facilities and infrastructure. Therefore, cooperation between various parties, including law enforcement officials, the community, and families, is needed to ensure the effectiveness of the diversion policy in the child criminal justice system in Indonesia. Keywords: Diversion; Juvenile Criminal Justice System; Restorative Justic